Noradrenergic control of error perseveration in medial prefrontal cortex - Caetano, Marcelo S.; Jin, Lu E.; Harenberg, Linda; Stachenfeld, Kimberly L.; Arnsten, Amy F.; Laubach, Mark (Frontiers in Integrative Neuroscience, 2013)
The medial prefrontal cortex (mPFC) plays a key role in behavioral variability, action monitoring, and inhibitory control. The functional role of mPFC may change over the lifespan due to a number of aging-related issues, including dendritic regression, increased cAMP signaling, and reductions in the efficacy of neuromodulators to influence mPFC processing. A key neurotransmitter in mPFC is norepinephrine. Previous studies have reported aging-related changes in the sensitivity of mPFC-dependent tasks to noradrenergic agonist drugs, such as guanfacine. Here, we assessed the effects of yohimbine, an alpha-2 noradrenergic antagonist, in cohorts of younger and older rats in a classic test of spatial working memory (using a T maze). Older rats (23-29 mo.) were impaired by a lower dose of yohimbine compared to younger animals (5-10 mo.). To determine if the drug acts on alpha-2 noradrenergic receptors in mPFC and if its effects are specific to memory-guided performance, we made infusions of yohimbine into mPFC of a cohort of young rats (6 mo.) using an operant delayed response task. The task involved testing rats in blocks of trials with memory- and stimulus-guided performance. Yohimbine selectively impaired memory-guided performance. Infusions of muscimol (a GABA-A agonist) at the same sites selectively impaired memory-guided performance, but did not lead to error perseveration. Based on these results, we propose several potential interpretations for the role for the noradrenergic system in the performance of delayed response tasks, including the encoding of previous response locations, task rules (i.e. using a win-stay strategy instead of a win-shift strategy), and performance monitoring (e.g. prospective encoding of outcomes).